2017
DOI: 10.1016/j.biomaterials.2016.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Shifts in macrophage phenotype at the biomaterial interface via IL-4 eluting coatings are associated with improved implant integration

Abstract: The present study tests the hypothesis that transient, early-stage shifts in macrophage polarization at the tissue-implant interface from a pro-inflammatory (M1) to an anti-inflammatory/regulatory (M2) phenotype mitigates the host inflammatory reaction against a non-degradable polypropylene mesh material and improves implant integration downstream. To address this hypothesis, a nanometer-thickness coating capable of releasing IL-4 (an M2 polarizing cytokine) from an implant surface at early stages of the host … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
155
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 178 publications
(166 citation statements)
references
References 73 publications
6
155
0
Order By: Relevance
“…The population which was present at the 7‐day time point was found to express significantly less Arg‐1 and significantly more iNOS in 18‐month‐old mice as compared to 8‐week‐old, suggesting a more M1‐like proinflammatory profile. Previous studies have shown the 7–14‐day postimplantation time frame to be significantly predictive of downstream outcomes, with higher numbers of M2 polarized cells and higher ratios of M2:M1 cells as indicators of improved integration and remodeling . Thus, this finding indicates the potential for poor downstream integration and remodeling in 18‐month‐old mice.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…The population which was present at the 7‐day time point was found to express significantly less Arg‐1 and significantly more iNOS in 18‐month‐old mice as compared to 8‐week‐old, suggesting a more M1‐like proinflammatory profile. Previous studies have shown the 7–14‐day postimplantation time frame to be significantly predictive of downstream outcomes, with higher numbers of M2 polarized cells and higher ratios of M2:M1 cells as indicators of improved integration and remodeling . Thus, this finding indicates the potential for poor downstream integration and remodeling in 18‐month‐old mice.…”
Section: Discussionmentioning
confidence: 62%
“…1985) were observed. A power analysis was performed to determine that 7 animals per group was required to maintain a statistical power of at least 80%, based on previous studies using the same model …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…permanent implants versus regenerative medicine-based approaches to tissue reconstruction) [13,3036]. As a result, multiple strategies have now been devised to promote shifts in macrophage phenotype at the host-tissue interface.…”
Section: Introductionmentioning
confidence: 99%
“…Future work will investigate the interplay between additional cell types present in the culture such as neurons and microglia. Potential future studies may also examine drug interactions (anti-inflammatory drugs that modulate macrophage (40, 41) or astrocyte behavior (42)), BBB breach (by incorporating IgG or blood borne macrophages in the culture), and incorporation of live cell imaging techniques to further understand the drivers and dynamics of glial scar formation within this model.…”
Section: Discussionmentioning
confidence: 99%